Vulnerabilidade ambiental da bacia hidrográfica do Rio Mutum (Pantanal Norte - Brasil) - Mello, Ana de Paula Gonçalves (2016)
One of the main concerns with land uses is erosion processes, especially when they are inadequately carried out in vulnerable places, leading to environmental, social and economic problems. The uses practiced in plateau areas around the Pantanal and in Pantanal itself can have effects on floodplains where all dynamics of land use and occupation have close relations with the flood pulse. The objective of this work was to carry out the zoning of the environmental vulnerability of the Mutum river basin establishing its relations with the different uses of the land and to analyze the relationship between soil loss and sediment transport and deposition processes in Sinhá Mariana bay near mouth of the river Mutum. This basin (16 ° 22'58 "S and 55 ° 48'90" 0) occupies the geomorphological units of the Guimarães plateau and part of the Pantanal plain of Mato Grosso. The methodology of environmental vulnerability zoning proposed by Crepani et al. (2001) adapted with the inclusion of the flood theme. For each of the six themes were established classes and assigned weights according to the potential of pedogenesis and morphogenesis, then the vulnerability synthesis map was generated. Using methods and techniques of geoprocessing in a GIS environment, the drainage network, the boundary and slope of the basin, and vulnerability maps were elaborated from the orbital images and vector data through LEGAL programming. Two top - height surveys were obtained and information was obtained on the contribution of suspended sediments, net flow estimation, total solid and granulometric types in the dry and full season, aiming at the general characterization of the Mutum - Sinhá Mariana bay system. The environmental vulnerability of the Mutum river basin ranged from stable to vulnerable reaching a maximum grade coefficient of 2.7 in the most vulnerable places. The stable class occupied an area of 3.95 km2 (slightly less than 1%), moderately stable 363.92 km2 (12%), moderately stable-vulnerable 2,225.44 km2 (65%), moderately vulnerable 930.56 km2 (21%) and vulnerable 6.15 km2 (less than 1%). In the plateau the class of vulnerability to soil loss that occupies most of this geomorphological unit is the moderately stable-vulnerable class where agriculture is practiced. At the edges of the plateau can be identified areas with moderate vulnerability and in places with greater slope of the terrain there was also moderate vulnerability. In the plain, most of this unit is moderately stable-vulnerable, but moderate vulnerability and vulnerability were observed in flood areas and close to river channels, especially those where land use is cattle ranching. The results of topobatimetry suggest that there was a progression of sedimentation of the bay, which may have been potentiated due to the land uses developed in the floodplain of the Mutum and plateau basins. The results of the liquid and solid flow analyzes and the bottom granulometric types (silt and clay) of the Sinhá Mariana bay corroborate this indication. The zoning of the environmental vulnerability in the Pantanal and elevated areas of its surroundings can subsidize management plans that aim to mitigate the erosive processes in this type of system. The analysis of the environmental vulnerability of the Mutum river basin has made it evident that soil erosion losses can be intensified if the management practices are not respected. Soil losses in both the plain and adjacent plateau can contribute to changes in river systems due to sedimentation and sedimentation, as well as to compromise the different uses of water and land in these two geomorphological units.